Short Biography of the Life and Work of Late Dr. Alexander Gibson - Vartak, V. D.; Chitnis, B. K. (Indian Forester, 1971)
The paper deals with a short biography of a renowned botanist Dr. Alexander Gibson who was the first Conservator of Forests of the then Bombay Presidency. Most of the life of Dr. Gibson while in India was devoted to conservation of forests of the Deccan Trap Country. His most valuable contribution is the creation of a monumental forest garden of indigenous and exotic species located at Hivare, (11Â°, 19' Nand 73Â°,03' E) in the Poona District, India.The paper further deals with details of gardens, its situation, general aspect of the vegetation and the importance of forest garden to this part of country.There is a likelihood of total submergence of this garden due to Kukadi River Valley project which may be implemented in the Fourth Five Year Plan period. The authors suggest a plan for the creation of similar garden elsewhere.